Mindfulness in the Academy Practices and Perspectives from Scholars (Springer Singapore, 2018)
This book focuses on the way academics understand, embrace and enact the concepts of mindfulness in approaching their work in demanding and dynamic contemporary higher education environments. It examines how they implement formal and informal mindfulness practices that increase the capacity to transform mind and body states by drawing on concepts such as compassion, kindness, gratitude, curiosity, self-awareness and non-judgemental stances. The book provides insights into and highlights the struggles of scholars through their experiences and perspectives in relation to their identities, practices and job enactment. Each chapter author explains their mindfulness practices and their motivations for implementing them, and explores how mindful ways of researching, writing, learning and teaching, leading, and engaging with others leads us to self-awareness and engagement in the present.